Biological activities of saliva extract from the medicinal Malaysian leech hirudinaria manillensis - Abdualkader, Abdualrahman M. (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2012)
The work presented in this thesis describes selected biological activities of the salivary gland secretion of the medicinal Malaysian leech Hirudinaria manillensis (Lesson, 1842). A new device for leech feeding was developed using common laboratory tools consisting of a glass funnel wrapped with a parafilm membrane and filled with the phagostimulatory solution. Many phagostimulatory solutions were examined and only those containing sodium chloride and arginine were accepted by leeches. It was found that 71% of the tested leeches continued sucking for 15-45 min and 86% of them experienced 1-5 folds increments in body weight. For collection of a high quality and quantity LSE, we starved leeches for three weeks. A new method for LSE collection was described. The fed leeches were forced to regurgitate whatever they sucked by immersing them in ice containers. By using this method, leeches stayed alive and regain their activity after 15-30 min. The maximum concentration (A280 = 0.342) was provided within the first five minutes of sucking action. Gel electrophoresis (SDSPAGE and Tricine-SDS-PAGE) methods revealed the existence of various peptides and proteins with molecular weights ranging from 2.3-250 kDa. Amidolytic activity assay showed that LSE inhibited thrombin-induced release of p-nitroanilide from the synthetic substrate S-2238 with IC50 of 49.391±2.219 μg/ml. LSE was shown to prolong thrombin time in vitro. The maximum antithrombin activity was obtained during the dry season (IC100 =16.081±0.079 μg/ml). A longer starvation period yielded a lower antithrombin activity. An optimization of lyophilization conditions revealed that pre-freezing at -20C and a lyophilization cycle of 24 hours produced a dried leech saliva extract with antithrombin activity similar to that of the fresh extract. Findings also showed that the best stability was achieved when the lyophilized leech saliva extract was stored at -20C in a dark place and glass tubes with loss of activity less than 10% during the study period of six months. Leech saliva showed an antibacterial activity against Sal. typhi and S. aureus with MIC of 78.353 μg/ml and against E. coli with MIC of 119.691 μg/ml. Disc diffusion test showed that leech saliva extracted from 16-week starved leeches exhibited zones of inhibition of 22 and 25 mm against Sal. typhi and E. coli. Starvation period was found to have a serious impact on the antimicrobial activity of leech saliva. No activity was observed against the fungal strains, C. albicans and C. neoformans. Dose responsive curve of the DPPH free radical scavenging method showed an antioxidant activity of LSE with IC50 of 7.282 μg/ml. The antidiabetic activity of subcutaneously injection of LSE (500 or 1000 μg/kg b.w) significantly reduced blood glucose in alloxan-induced diabetic rats. LSE at the mentioned doses had no toxic events. The concurrent injection of LSE (250 μg/kg b.w) and insulin (10 units/kg b.w) led to a good control in the glycemic states of the experimental rats with an instant decrease in blood glucose of 80-90% during the whole period of the study. Injection of LSE (250 μg/kg b.w) one hour prior to alloxanisation (160 mg/kg b.w) prevented diabetes induction in the experimental rats. Nevertheless, double doses of alloxan produced mild diabetic states. Leech saliva extract exhibited a cytotoxic activity against small cell lung cancer (SW1271 cell line) with IC50 of 119.844 μg/ml compared to the IC50 values of two reference standard drugs, Irinotecan (5.813 μg/ml) and Carboplatin (18.754 μg/ml). LSE reduced the IC50 of Carboplatin and Irinotecan by 65% and 11.5% respectively. Carboplatin reduced the IC50 of LSE by 4.6%. Irinotecan was found to decline IC50 of LSE by 57%.